UPAYA PENINGKATAN KINERJA BAGIAN UNIT I PIDANA UMUM SATUAN RESERSE KRIMINAL (SAT RESKRIM) POLRES MAGELANG KOTA - Saputro, Ginanjar; Syaflan, Meidi (Jurnal Riset Manajemen Akuntansi Indonesia, 2024)
The performance of the Police Apparatus in the Criminal Investigation Unit (Sat Reskrim) in the General Criminal Unit I (Pidum) of the Magelang City Police still encountered several obstacles in improving its performance, it is necessary to conduct this study with the aim of knowing and describing the performance of the Criminal Investigation Unit (Sat Reskrim) in The General Crime Unit I (Pidum) of the Magelang City Police is still not optimal and to formulate efforts to improve the performance of the Criminal Investigation Unit (Sat Reskrim) in the General Crime Unit (Pidum) of the Magelang City Police. This research is a qualitative research with 3 resource persons and analyzed using interactive model data as proposed by Miles and Huberman. The results showed that the performance of the General Criminal Unit I of the Criminal Investigation Unit (Sat Reskrim) of the Magelang City Police was good with Humane and Qwick Response efforts, especially in carrying out investigative tasks, where investigators were authorized to arrest, detain, search, confiscate and examine letters, but still there are several things that are not optimal, namely criminal acts that often occur in the community in 2020 as many as 115 incoming case reports and only 82 cases were able to be resolved, so that 33 cases have not been resolved, besides that what has not been achieved according to the target is the implementation of nine superior programs Central Java Police that must be carried out by the Magelang City Police. Then efforts to improve the performance of personnel in Unit I Sat Reskrim Polres Magelang City, especially in the Investigation section, are as follows: guidance and direction, training and Personnel Development, preparing certain personnel to occupy existing jobs in accordance with the skills possessed. To improve personnel performance, discipline against the rules to achieve high organizational efficiency and effectiveness and to reward services or loyalty to the organization, both material and immaterial.